The thing of mine I have loved the best meaningful jewels - Hahn, Cynthia J. 1952-; Chadour-Sampson, Anna Beatriz 1953- (Les Enluminures, 2018)
"This book studies forty-six pieces of European jewelry-pendants, reliquaries, amulets, and talismans-from the eighth to the eighteenth century. The engaging title "The thing of mine I have loved the best" comes from the medieval will of an English duchess who bequeaths a reliquary jewel to her son. It expresses the sentiment that jewels appealed (then, as well as now) to the truest and strongest emotions."--Front jacket flap
Published for Les Enluminures by Paul Holberton Publishing. - Catalogue for an exhibition held from March 8 to 18, 2018, at TEFAF Maastricht, Stand 276, MECC, Forum 100, Maastricht, The Netherlands, and from April 5 to 20, 2018, at Les Enluminures Ltd., New York, NY. - Includes bibliographical references (pages 349-363)
Keywords: Geschichte; Andenken; Schmuck; Reliquiar; Jewelry / Exhibitions / Europe; Reliquaries / Exhibitions / Europe; Christian art and symbolism; Ausstellungskatalog -- TEFAF -- 08.03.2018-18.03.2018 -- Maastricht; Ausstellungskatalog -- Les Enluminures Ltd -- 05.04.2018-20.04.2018 -- New York, NY